Genesis, institutions and instruments of the European Union a concise guide on Euro-multilateralism - Bajrektarevic, Anis H. <<[VerfasserIn]>>; Wolf, Nora <<[VerfasserIn]>> (New York Nova Science Publishers, 2022)
"This reader is designed to be a concise summary of the history of the European Union. Starting with the rebirth of a common European vision right after WWII, this reader will elaborate on all the vital events and treaties that have come to substantially shape the course of the European Union to the point where it is today. Due reference is devoted to the current state-of-arts of the Union too (critically, but fairly and objectively assessed). Even though the European Union considerably contributes to improved living conditions being the form and the substance for European citizens and is commonly accepted as a heavy-weight tool on the global political stage, it is yet to fully realize its capacities. The present reader does not seek to take position nor to make a case that the precise institution that came to be known as the European Union shall be exempt of criticism and questioning. Instead, the authors wish to convey an idea and an understanding of a real-life model, an essence of transnational cooperation. As such, it is objectively valuable to learn it and learn from it in order to give a chance to the widest range possible of actors to fuel the current or future discussions on multilateral cooperation possibilities world-wide, understood here as a means to join forces in solidarity and reach common goals"--
Includes bibliographical references and index